2015
DOI: 10.1002/bjs.9724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local injection of mesenchymal stem cells on healing of sutured gastric perforation in an experimental model

Abstract: Local injection of mesenchymal stem cells was more effective than topical application, and enhanced the healing of sutured gastric perforations by an anti-inflammatory process, enhanced cellular proliferation and earlier onset of granulation. Surgical relevance Abnormal healing of gastric perforation may cause morbidity and increase the risk of death. Adipose tissue-derived mesenchymal stem cells have been found to promote the healing of organ injuries through cellular differentiation and secretion of cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
(31 reference statements)
1
33
1
Order By: Relevance
“…Intestinal repair is a complex process that involves stromal-epithelial cell communication to restore the integrity of the bowel wall. Myofibroblasts are stromal cells of the gastrointestinal (GI) tract that are a known target of inflammatory mediator signaling [14] and appear to play an important role in restoring intestinal homeostasis [57] Myofibroblasts migrate to areas of injury, and interact with the overlying epithelium to regulate cell proliferation as well as deposition and remodeling of the underlying extracellular matrix [6, 811]. …”
Section: Introductionmentioning
confidence: 99%
“…Intestinal repair is a complex process that involves stromal-epithelial cell communication to restore the integrity of the bowel wall. Myofibroblasts are stromal cells of the gastrointestinal (GI) tract that are a known target of inflammatory mediator signaling [14] and appear to play an important role in restoring intestinal homeostasis [57] Myofibroblasts migrate to areas of injury, and interact with the overlying epithelium to regulate cell proliferation as well as deposition and remodeling of the underlying extracellular matrix [6, 811]. …”
Section: Introductionmentioning
confidence: 99%
“…Enhanced healing of gastric perforation by PEI/PAA powder treatment. To further demonstrate that the PEI/PAA powder can be used as sealants to treat gastrointestinal perforation, we used an in-vivo rat gastric perforation model [42][43][44] (Fig. 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the ability of MSCs to preferentially migrate to sites of injury when infused in animal models (2729). After receiving appropriate signals during tissue inflammation, MSCs could migrate to the lesions of the colon where they assisted in recovery, displaying high therapeutic potential with regards to tissue repair and/or the control of local inflammation (30). The expression of growth factors, cytokines and extracellular matrix receptors by MSCs may drive this process (31,32).…”
Section: Discussionmentioning
confidence: 99%